Genetic diversity in lens species revealed by EST and genomic simple sequence repeat analysis - Dikshit, Harsh Kumar; Singh, Akanksha; Singh, Dharmendra; Aski, Muraleedhar; Prakash, Prapti; Jain, Neelu; Meena, Suresh; Kumar, Shiv; Sarker, Ashutosh (Public Library of Science, 2015)
Low productivity of pilosae type lentils grown in South Asia is attributed to narrow genetic base of the released cultivars which results in susceptibility to biotic and abiotic stresses. For enhancement of productivity and production, broadening of genetic base is essentially required. The genetic base of released cultivars can be broadened by using diverse types including bold seeded and early maturing lentils from Mediterranean region and related wild species. Genetic diversity in eighty six accessions of three species of genus Lens was assessed based on twelve genomic and thirty one EST-SSR markers. The evaluated set of genotypes included diverse lentil varieties and advanced breeding lines from Indian programme, two early maturing ICARDA lines and five related wild subspecies/species endemic to the Mediterranean region. Genomic SSRs exhibited higher polymorphism in comparison to EST SSRs. GLLC 598 produced 5 alleles with highest gene diversity value of 0.80. Among the studied subspecies/species 43 SSRs detected maximum number of alleles in L. orientalis. Based on Nei's genetic distance cultivated lentil L. culinaris subsp. culinaris was found to be close to its wild progenitor L. culinaris subsp. orientalis. The Prichard's structure of 86 genotypes distinguished different subspecies/species. Higher variability was recorded among individuals within population than among populations.